Functional Restoration of Exhausted CD8 T Cells in Chronic HIV-1 Infection by Targeting Mitochondrial Dysfunction - Alrubayyi, Aljawharah; Moreno-Cubero, Elia; Hameiri-Bowen, Dan; Matthews, Rebecca; Rowland-Jones, Sarah; Schurich, Anna; Peppa, Dimitra (Frontiers in Immunology, 2022)
CD8 T cell exhaustion is a hallmark of HIV-1 infection, characterized by phenotypic and functional CD8 T cell abnormalities that persist despite years of effective antiretroviral treatment (ART). More recently, the importance of cellular metabolism in shaping T cell antiviral function has emerged as a crucial aspect of immunotherapeutics aimed at re-invigorating exhausted CD8 T cells but remains under-investigated in HIV-1 infection. To gain a better insight into this process and identify new targets for effective CD8 T cell restoration we examined the metabolic profile of exhausted CD8 T cells in HIV-1 infection. We show that relative to HIV-1 elite controllers (EC) and HIV-1 seronegative donors, CD8 T cells from HIV-1 viraemic individuals are skewed toward a PD-1hiEOMEShiT-betLoTIGIT+ phenotype that is maintained during ART. This exhausted signature is enriched in HIV-specific CD8 T cells, compared to CMV-specific CD8 T cell populations, and further delineated by higher expression of the glucose transporter, Glut-1, impaired mitochondrial function and biogenesis, reflecting underlying metabolic defects. A notable improvement in antiviral HIV-specific CD8 T cell function was elicited via mitochondrial antioxidant treatment in combination with pharmacological modulation of mitochondrial dynamics and IL-15 treatment. These findings identify mitochondria as promising targets for combined reconstitution therapies in HIV-1 infection.